Genetics of association among yield and blast resistance traits in rice (Oryza sativa) - B, DIVYA; S, ROBIN; A, BISWAS; A, JOHN JOEL (The Indian Journal of Agricultural Sciences, 2015)
Blast disease caused by the fungus Pyricularia oryzae is one of the serious threats to world's most important staple food crop, rice (Oryza sativa L.). The improvement of blast resistance is one of the priority areas in breeding. Knowledge about association of yield traits with resistance parameters should be of paramount importance prior to development of a high yielding resistant variety. The present study was designed to understand the association of different traits in the segregating generations (F3 and BC2F1) developed from a high yielding rice variety ADT 43 and a blast resistant Near Isogenic Line (NIL), viz. CT13432-3R. The associations among traits related to yield and blast resistance were investigated. The correlation and path analysis have shown that characters like lesion type, potential disease incidence, lesion number and infested leaf area has significant positive correlation and high positive direct effect with leaf blast susceptibility. Therefore it was concluded that selecting genotypes with lower lesion number, high seedling vigour and short compact panicles with less exertion are preferable to reduce leaf blast disease incidence. Single plant yield was positively correlated with plant height, number of productive tillers, panicle length and filled grains per panicle. The highest genotypic association to grain yield was contributed by number of productive tillers. Selection of genotypes for these traits will ultimately result in increased yield.